Collection building in academic libraries in India: status, challenges and way forward. (26th September 2019) - Ansari, Mehtab Alam
Abstract : Purpose: The purpose of this paper is to highlight the status and application of automated acquisition in central university libraries in north India. North India is a loosely defined region consisting of northern parts of India. Significantly, all the libraries are having very rich collections of different types of documents. Design/methodology/approach: Data for the present study have been collected using questionnaire. Interview and observation techniques have also been used to bring more objectivity in the present study. MS-Excel has been used for analysis of the data. Results show that varying levels of progress has been made with respect to implementation of acquisition system in the surveyed libraries. Findings: Expectations of user community have been increased manifold in the wired world. Furthermore, suggest that the staff morale is boost up in the automated environment. Research limitations/implications: The study covers select academic libraries of north India. Application of various features of acquisition module is examined in this paper along with the staff perspective about automation. Automation process in these university libraries has been started with the selection of different library management software package in different universities. Notably, all the prominent central universities are located in north India. Practical implications: The evaluation shed light on the current automation scenario in prominent academic libraries of India. Social implications: All the surveyed libraries must explore the fullest potentials of all the features available in the software to provide better services. This will help in heading toward and information rich society. Originality/value: There have been a couple of studies in the past on library automation in academic libraries, but none have intended to cover collection building or acquisition activities in central university libraries of north India.